Alkaloid Furokuinolin dan Asam Sinamat Ter-O-Geranilasi dari Kulit Batang Melicope hookeri T.G. HARTLEY - Ratih Dewi Saputri; Tjitjik Srie Tjahjandarie; Mulyadi Tanjung (Fakultas Farmasi, Universitas Mulawarman, Samarinda, Indonesia, 2019)
One furokuinoline alkaloid, evolitrine (1), and one cinnamate acid, trans 3-methyl-4-geranil caffeic acid (2) were isolated from the stem bark of Melicope hookeri. The structures of both compounds were determined based on spectroscopic data such as UV, IR, MS and NMR. Compounds 1–2 were evaluated for their anticancer activity against murin leukemia P-388 cells, showing their IC50 were 4,06 ± 0,15 and 4,86 ± 0,30 µg/ml, and two compounds showed moderate activity.